THE IMPROVEMENT OF HIGH EDUCATION QUALITY IN INDONESIA THROUGH THE CHARACTER EDUCATION - Ieke Sartika Iriany; Rostiena Paciana (Journal Of Educational Experts (JEE), 2019)
Nowadays, moral education or character education; has become a relevant way to resolve moral crisis happens in Indonesia. When we said about moral crisis, it all refers to corruption, fornication, children and teen abuse, peer to peer violence, juvenile delinquency, the habit of cheating in exam, drugs abuse, pornography, and anarchy. All of it has become social problems that we still do not have the answer on how to resolve. Thus, based on the matter, character education obviously becomes an important thing to be implemented. Objective description that factually happen to the Indonesian nowadays, has show us that The Indonesian almost lost its true self (or identity).  Many incidents happened in a last years, had threatened the nation existence. The spread of social conflict and terror had destroyed the social capital, which is important for the community moral integration. In other side, corruption, collusion and nepotism have turned this nation to become a low trust society. Based on the objective description above, I thought we need to improve the quality of higher educations, particularly through the character education; thus, they could result a diplomas with strong Indonesian identity. Nation Identity will be appears in the nation’s character as an implementation of the highest value of the nation. For the Indonesian, the highest values of the nation clearly written in the national principle, which is Pancasila.  Pancasila itself, is the establishment of religious, humanity, nationalism, sovereignty, and sociality concepts. Revitalization of Indonesian identity mean, re-build and strengthen Indonesian identity to every citizens. In other words, an effort to build a person with strong Pancasila sense whom has moral and responsible. Higher education level, in this case, has responsibility to shape and strengthening the national identity, which nowadays seems to be weakened.